Le Conseil économique du Canada et le modèle CANDIDE - Dawson, J.; Wale, N. (L'Actualité économique, 1975)
AbstractThe CANDIDE model has been used by the Economic Council to examine Canada's economic potential, to analyze the effects of economic forces, and to consider the appropriateness of alternative policies in reaching economic objectives. For its Annual Reviews, the model provides an analytical basis for taking into account the interdependence of a number of phenomena, including those related to demographic trends, external economic conditions and domestic policies influencing supply and demand, and thus facilitates estimation of the potential development of the economy over the longer term. Within this context, a realizable set of medium-term objectives can then be established. These have been presented by the Council as performance indicators for the three years immediately ahead and they are subsequently used to monitor and assess economic developments. The model also is used by the Council to examine how various economic influences work their way through the Canadian economy. In its Annual Reviews, for example, the effects of alternative scenarios for energy investment and prices have been considered. In a special study of the construction industry, the model was used to trace the causes and effects of instability in this sector. Some illustrative results from each of these impact studies are provided. The model has also been employed to explore the implications of certain past and future changes in commercial policy, including separating out the impact of the Canada-United States Automobile Agreement, and in examining changes that have been taking place in labour markets. Each of these areas have been the subject of special studies carried out by the Council.